Eukaryotic pathogens (Chytridiomycota and Oomycota) infecting marine microphytobenthic diatoms – a methodological comparison. Issue 6 (18th September 2014) - Scholz, Bettina; Küpper, Frithjof C.; Vyverman, Wim; Karsten, Ulf; Kroth, P.
<x xml:space="preserve">Abstract</x> Using sediment samples from the Solthörn tidal flat (southern North Sea, Germany), collected in bi‐weekly intervals from June to July 2012, a range of qualitative and quantitative screening methods for oomycete and chytrid pathogens infecting benthic diatoms were evaluated. Pre‐treatment of sediment samples using short ultrasound pulses and gradient centrifugation, in combination with CalcoFluor White, showed the best results in the visualization of both pathogen groups. The highest number of infected benthic diatoms was observed in mid July (5.8% of the total benthic diatom community). Most infections were caused by chytrids and, in a few cases, oomycetes (Lagenisma Drebes (host: Coscinodiscus radiatus Ehrenberg) and Ectrogella Zopf (hosts: Dimeregramma minor in Pritchard and Gyrosigma peisonis). Among the chytrids, sporangium morphology indicated the presence of five different morphotypes, infecting mainly epipelic taxa of the orders Naviculales (e.g., Navicula digitoradiata) and Achnanthales (e.g., Achnanthes brevipes Agardh). The presence of multiple pathogens in several epipelic diatom taxa suggests a significant role for fungal parasitism in affecting microphytobenthic diatom succession.